Examining the Association between Psychopathic Traits and Fearlessness among Maximum-Security Incarcerated Male Adolescents - J. Michael Maurer; Nathaniel E. Anderson; Corey H. Allen; Kent A. Kiehl (MDPI AG, 2024)
Studies have reported positive associations between youth psychopathy scores and measures of 'fearlessness'. However, prior studies modified fearlessness items to be age appropriate, shifting from assessing hypothetical, extreme forms of physical risk-taking (e.g., flying an airplane) to normative risk-taking (e.g., riding bicycles downhill). We hypothesize that associations between youth psychopathy scores and alternative forms of sensation seeking (i.e., Disinhibition) have been conflated under a false fearlessness label. We tested this hypothesis among incarcerated male adolescents, investigating whether youth psychopathy scores were significantly associated with two different forms of sensation seeking: Disinhibition and Thrill and Adventure Seeking (TAS). Youth psychopathic traits were assessed using the Psychopathy Checklist: Youth Version (PCL:YV), Antisocial Process Screening Device (APSD), Child Psychopathy Scale (CPS), Inventory of Callous and Unemotional Traits (ICU), and Youth Psychopathic Traits Inventory (YPI). Disinhibition and fearlessness (i.e., TAS) were assessed using an unmodified version of the Zuckerman Sensation Seeking Scales (SSS). Consistent with hypotheses, youth psychopathy scores were associated with higher Disinhibition and lower TAS scores. Our results contribute to a growing body of literature suggesting that psychopathic traits, including among adolescents, are not concomitant with physical risk-taking and descriptions of psychopathy including fearlessness distort a precise understanding of psychopathy's core features.